Ma trận Toeplitz và mã bình phương tối thiểu cho các đường cong số hóa - Mai, Luong Chi; Sloboda, Fridrich (Journal of Computer Science and Cybernetics, 2018)
Digital contour coding is described. The coding technique is associated with the maximal feasible smoothing operator which smooths the ogirinal simply closed 4-connected digital  curve in the least – squares sense. This smooting operator generates 272 permissible direction vectors. For the realization of the resulting coding technique a pipeline architecture has been suggested which operates with high cloch frequency.